Visceral Leishmaniasis (Anew Approach in diagnosis) - AI-Ma key, M.K.H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This StudyÂ· is to investigate the Visceral LeishmaniEJ,sis among 8 susp<:;cted infants and young chUdren admitted 1o AI-Khadhtmiya Pediatric Hospital in Baghdad between January 1,2005 o August 31,2005 .For each patieni, a medical history was obtained and a complete physical examination was performed by physicians . The serums of the .suspected c_es were primarily diagnosed by using a new ,simple diagnostic method bas.ed on detecting antib9dies against the recombinant K 39 antigen by innnunochromatographic format (Dipstick test). The positei cases. were sent to the Central Health Laboratory in Baghdad to he confirmed by indirect fluorescent antibody test QFAT)with speCial chart for notifying the patient’s residency in details . The ihcidence of infection was (J 2%)1 most patients were from males and the majority of cases were from Baghdad .The study also showed the investigators evaluation for performance of the test and its s nsitivity and specificUy in different endemic areas which proved that the test is Â·a new, simple ,and specific reli_a le diagnostic method and ()oulcl _be used for the primary diagnosis ,of endemie foci in remote areas which have poor access to health services _